Digital Video Virtual Tours as a Potential Factor Considered by Tourists Visiting Bali - Bendesa, I Wayan Pariasta; Sutapa, I Ketut; Isyoratullatifah; Ardani, Ni Nyoman (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
Rapid technological advancement has positioned digital video as a mainstream medium for experiencing the beauty of tourism destinations. For middle-class tourists, these videos serve as inspiration to visit in person, while for individuals with limited financial resources, they offer a virtual substitute for real travel experiences. This study aims to analyze the extent to which virtual tourism videos influence the perceived image of a destination. A total of 62 respondents participated in the research, comprising tourism practitioners, travel agency clients, and visitors to Bali. Using multiple linear regression analysis, the study explored three independent variables, video quality, features, and language, and their relationship to the dependent variable: the image of the tourism destination. The findings reveal that digital video quality and features have a positive and significant impact on a destination’s image, whereas the language used in the video does not exert any influence. The study's implications suggest that destination managers should prioritize the enhancement of digital video quality and feature richness when promoting tourism offerings. Additionally, the public should be well-informed about the advantages of digital video in making informed decisions when selecting travel destinations.